2013
DOI: 10.2147/ott.s41711
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative neutrophil-lymphocyte and platelet-lymphocyte ratios as independent predictors of cervical stromal involvement in surgically treated endometrioid adenocarcinoma

Abstract: BackgroundThe purpose of this study was to evaluate the relationship between preoperative inflammatory markers (neutrophil-lymphocyte ratio and platelet-lymphocyte ratio) and cervical stromal involvement in patients with endometrioid adenocarcinoma.MethodsWe studied 318 patients with endometrioid adenocarcinoma who underwent comprehensive surgical staging. We used univariate and multivariate analyses of cervical stromal involvement and receiver-operating curves to calculate optimal cutoff values for neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 19 publications
(24 reference statements)
1
43
0
Order By: Relevance
“…It was found that PLR has better prognostic value than platelet or lymphocytes alone in predicting certain cardiovascular diseases [23]. We found that PLR was significantly higher for patients who died within 30-days of hospital admission in the univariate analysis.…”
Section: Discussionmentioning
confidence: 61%
“…It was found that PLR has better prognostic value than platelet or lymphocytes alone in predicting certain cardiovascular diseases [23]. We found that PLR was significantly higher for patients who died within 30-days of hospital admission in the univariate analysis.…”
Section: Discussionmentioning
confidence: 61%
“…In the report by Suh et al, the cutoff value of NLR was 1.97 [29]. Regarding the prediction of cervical stromal invasion, in the report of Wang et al [16], the cutoff value was 2.01. The cutoff value in our study was 2.18, which is close to the previous report.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence has not been confirmed due to the small number of cases. Another report suggested predictors of cervical stromal invasion in endometrial cancers [16]. However, there have been studies to assess whether inflammatory markers could be independent predictors of survival or LN metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study revealed that even though there were no difference between platelet counts between EC and control groups, the mean platelet volume which is one of morphological parameters of platelet, is higher in EC group than normal control groups [ 14 ]. On the other hand, Wang et al [ 15 ] reported that NLR and PLR were found higher in patients with EC with cervical stromal invasion, and suggested the evaluation of these ratios may help select patients who should be particularly watched and tested for cervical stromal involvement.…”
Section: Discussionmentioning
confidence: 99%